Poltik dan perempuan: Peran politik perempuan, pentingnya pendidikan politik perempuan - Abidin, Zaenal (Maliki Interdisciplinary Journal, 2024)
This journal aims to analyze how women are involved in the world of politics. Where women's participation in politics is relatively low due to several factors such as culture which emphasizes that women can only contribute in the family domain. Even though there are women in politics, they cannot have an optimal impact in society, few parties choose female cadres, parties admit that women are difficult to invite into politics and lack awareness of the importance of politics. However, in this millennial era, women's participation began to be seen in Indonesia, the first women's congress was held in Yogyakarta in 1928 and women's participation in the elections in 1955, demonstrated the right to vote and vote. For this reason, in order for women cadres in politics to increase, it is necessary to open up wide opportunities and possibilities for women and provide political education so that it is not only men who are involved in politics, women can also be involved in it for the sake of gender equality between men and women.